Therapeutic Communication For Children Victims of Sexual Violence in Citra Tepian-Samarinda - Rina Juwita; Kadek Dristiana Dwivayani; Najahatul Hananah (ARISTO, 2022)
The phenomenon of sexual violence against children shows an increase trend from year to year so it requires special handling to not cause psychological trauma that might affect their future. This was the reason behind the establishment of the Protection of Women and Children Unit by the government to handle cases relate to sexual violence which one of it is against children. By using a narrative qualitative approach, this research is conducted at the UPTD PPA Citra Tepian in Samarinda City to analyse the children trauma healing process psychologists must go through therapeutic communication which divided into 4 stages; namely pre-interaction, orientation, problem solving, and termination to get maximum results. This is very important fully help restoring a sense of security within the victim so that it will be easier for the child victim to re-enter and re-interact with their social environment. Therapeutic communication that emphasizes the interpersonal approach carried out by accompanying psychologists is believed to be an important key that determines the success of the 'trauma healing' process. However, it is necessary to pay more attention to the aspects of ethnicity, race, economy and culture of the victims so that the process can be more effective and efficient in the future